Contextualizing immigrant inter-wave dynamics and the consequences for migration processes: Ukrainians in the United Kingdom and the Netherlands - Kubal, A; Dekker, R (International Migration Institute, 2011)
What drives international migration? Theories of migration networks, migration culture, migration systems and cumulative causation suggest that once a critical threshold level of migrants have settled, migration tends to stimulate the creation of social and economic structures that make the process of migration self-perpetuating (cf. Massey et al. 1987; de Haas 2010). One important aspect of the theory is that the more migrants from a particular locality settle in one place, their presence, assistance and established structures in the destination country act as incentives for others to follow in their footsteps, which emphasizes the instrumental role of pioneers’ agency in influencing others to follow suit. A historical perspective on the migration from Ukraine to the United Kingdom and the Netherlands challenges this assumption. While substantial numbers of migrants have settled in those destinations, migration, especially in the last 20 years, has not developed into large, self-sustaining migration systems (in comparison to the dynamic migration linkages between Ukraine and Southern European countries such as Portugal, Italy and Greece). Trying to understand why migration has not taken off, we argue that the role of settled pioneer migrants and their community structures in assisting others to follow in their footsteps should not be taken for granted. We argue that the role of pioneers is much more ambiguous and complex, and the relevant question about 'bridgeheads’ and 'gatekeepers’ (cf. Böcker 1994) should not be that of 'either/or’ but 'how much’, 'to what extent’ or 'under what conditions’.